(untitled) (Signifiances (Signifying), 2021)
This article proposes a stratified realistic model as a general and comprehensive framework for a description of the human world experienced, as well as its strata and areas of experience. An attempt will be made to show how a psycho-semiotic study should be directly associated with an eco-semiotic study because the mind is itself shaped by the semiotic world with which it has evolved. Ethics, aesthetics, and critical thinking must now converge, in the light of contemporary threats, to defend the possibility of global and planetary humanity and habitat.